2014
DOI: 10.1002/2013ms000272
|View full text |Cite
|
Sign up to set email alerts
|

The moist static energy budget in NCAR CAM5 hindcasts during DYNAMO

Abstract: The Dynamics of the MJO (DYNAMO) field campaign took place in the Indian Ocean during boreal fall and winter of 2011-2012 to collect observations of Madden-Julian Oscillation (MJO) initiation. Hindcast experiments are conducted with an atmospheric general circulation model with varying values of a dilute CAPE entrainment rate parameter for the first two MJO events of DYNAMO from 1 October 2011 to 15 December 2011. Higher entrainment rates better reproduce MJO precipitation and zonal wind, with RMM skill up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
69
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 93 publications
(130 reference statements)
8
69
1
Order By: Relevance
“…In recent years, one popular way of thinking about the MJO is as a moisture mode [14,21] with many studies seeking to understand its mechanism(s) of moistening and drying [22][23][24]. The moisture mode concept is consistent with the observation that high rain rates are correlated with regions of high column integrated moisture in the tropics in general [25,26].…”
Section: Introductionmentioning
confidence: 84%
“…In recent years, one popular way of thinking about the MJO is as a moisture mode [14,21] with many studies seeking to understand its mechanism(s) of moistening and drying [22][23][24]. The moisture mode concept is consistent with the observation that high rain rates are correlated with regions of high column integrated moisture in the tropics in general [25,26].…”
Section: Introductionmentioning
confidence: 84%
“…This gap between parameterization development and improving model performance motivated the recent development of the 'process-oriented' MJO simulation diagnostics by the MJOTF and others (Maloney 2009;Kiranmayi and Maloney 2011;Andersen and Kuang 2012;Kim et al 2014Kim et al , 2015Benedict et al 2014;Chikira 2014;Hannah and Maloney 2014;Arnold and Randall 2015;Klingaman et al 2015a, b;Xavier et al 2015;Wolding and Maloney 2015;Wolding et al 2016). These process-oriented diagnostics are designed to characterize resolved-scale processes that are strongly affected by certain aspects of parameterization schemes, and that are relevant to MJO dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling studies have also been undertaken with operational forecasts Fu et al 2013;Ling et al 2014;Kerns and Chen 2014a) and global/regional model simulations (Fu et al 2015;Hannah and Maloney 2014;Miyakawa et al 2014;Nasuno 2013;Subramanian and Zhang 2014;Chen et al 2015;Hagos et al 2014a, b;Seo et al 2014;Wang et al 2015). With regard to the moistening process of the MJO, a special focus has been given on multi-scale processes (Chen et al 2015;Hagos et al 2014b;Kerns and Chen 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The moisture or moist static energy (MSE) budgets were assessed as a process-oriented diagnosis, in both observational Sobel et al 2014) and modeling (Hannah and Maloney 2014;Seo et al 2014;Subramanian and Zhang 2014;Wang et al 2015) studies. Sobel et al (2014) confirmed that the MSE budgets during the life cycle of the CINDY2011/ DYNAMO MJOs generally agreed with those reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%